Dynamically optimal R&D subsidization - Volker Grossmann; Thomas M. Steger; Timo Trimborn (Center for Economic Studies and ifo Institute (CESifo), 2010)
Previous research on optimal R&D subsidies has focussed on the long run. This paper characterizes the optimal time path of R&D subsidization in a semi-endogenous growth model, by exploiting a recently developed numerical method. Starting from the steady state under current R&D subsidization in the US, the R&D subsidy should significantly jump upwards and then slightly decrease over time. There is a negligible loss in welfare, however, from immediately setting the R&D subsidy to its optimal long run level, compared to the case where the dynamically optimal policy is implemented.
Keywords: H20; O30; O40; 330; R&D subsidy; transitional dynamics; semi-endogenous growth; welfare; Forschungssubvention; Dynamische Optimierung; Neue Wachstumstheorie; Intertemporale Allokation; Wohlfahrtseffekt; Theorie; USA